Students' Specializing Thinking in Solving Arithmetic Sequence and Series Problems - Lorenza, Nella; Sudirman, Sudirman; Susiswo, Susiswo (PRISMA, 2024)
Specializing thinking is a mathematical thinking process that is very important in the mathematics learning process. Specializing thinking is thinking by starting with special things. The application of specializing thinking can be an effective strategy for teachers to improve students' mathematical thinking abilities in dealing with various problems. This research aims to describe students' specializing forms of thinking in solving problems of arithmetic sequences and series. This research method is descriptive qualitative research with a case study approach. The subjects in this research were 2 class X high school students who successfully solved arithmetic sequence and series problems. The instruments used are tests and interviews. The data in this research are the results of the subject's work and the results of interview transcripts. The research results show that two forms of specializing thinking were found in solving arithmetic sequences and series problems, that is explicit schematic representation and implicit schematic representation. It is hoped that the results of this research can provide a valuable contribution to mathematics teachers in designing more meaningful learning.